Narrating the Generative Life - McAdams, Dan P.; Guo, Jen (Psychological Science, 2015)
Generativity is an adult’s concern for and commitment to promoting the well-being of future generations. Analyzing lengthy life-narrative interviews of late-midlife adults, we examined the extent to which a particular kind of life story is empirically linked to self-report measures of generativity and other indices of psychosocial adaptation in midlife. The results showed that highly generative adults are significantly more likely than their less-generative counterparts to construe their lives as variations on a prototypical redemption narrative, wherein the story’s protagonist (a) enjoys an early advantage in life, (b) exhibits sensitivity to the suffering of other people, (c) develops a clear moral framework, (d) repeatedly transforms negative scenes into positive outcomes, and (e) pursues prosocial goals for the future. The psychological and cultural features of redemptive life stories are considered, as are the problems and potentialities of life-narrative research in psychological science.